2021
DOI: 10.15280/jlm.2021.11.2.52
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Marketing to Promote Preventive Behaviors Related to COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), is an infectious disease caused by SARS-CoV-2 virus, a newly discovered coronavirus, the best strategy to deal with the infection is prevention aimed at reducing transmission in the community. This article aimed to using effective behavior change strategies are needed to control COVID-19. Social marketing facilitates the acceptance, rejection, modification, abandonment, or maintenance of particular behaviors by groups of individuals, often referred to as the target audience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The field of social marketing [18,19] has studied how to use communication strategies to persuade people to change their public health behaviors. Research on social media campaigns, has found that these campaigns can spread messaging, but there has been limited work on the extent to which social media campaigns change behavior [20,21].…”
Section: Short Messages As a Medium Of Persuasionmentioning
confidence: 99%
“…The field of social marketing [18,19] has studied how to use communication strategies to persuade people to change their public health behaviors. Research on social media campaigns, has found that these campaigns can spread messaging, but there has been limited work on the extent to which social media campaigns change behavior [20,21].…”
Section: Short Messages As a Medium Of Persuasionmentioning
confidence: 99%
“…Moreover, McKinney, [16] supported that the most important element to understand those behaviours is market segmentation, whilst Nejad et.al. [19] argued that regarding COVID-19, the public which is the main audience can be segmented into different age, job and sex groups, as well as into those with underlying disease which makes them more conscious to COVID-19. This study supported the above findings as it segments Greek citizens of Generation Y. known as millennials, according to their attitudes towards the impact of social marketing on the awareness of people regarding public health in general, and the fight against COVID -19 in particular, and profiled them according to their demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The benchmark criteria of social marketing interventions according to Nejadet.al. [19] are: behaviour change, customer research, audience segmentation, marketing mix exchange and competition whilst Olawepoet. al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation